Potential of fermented rumen content of cow feed on daily egg productivity and quality of yolk color of quail egg (Cortunix cortunix japonica) - Moh. Zaky ‘Ubaidillah; Mohammad Anam Al Arif; Tatik Hernawati; Koesnoto Supranianondo; Emy Koestanti Sabdoningrum; Widya Paramita Lokapirnasari (Universitas Airlangga, 2024)
The purpose of this study was to determine the effect of fermented rumen contents on quail rations. The parameters measured were daily egg production and egg yolk quality. There are 96 quails with 4 treatments and 6 repetitions. (T0) formulation feed without fermented rumen contents, (T1) formulation feed + 5% fermented rumen content, (T2) formulation feed + 10% fermented rumen content, (T3) formulation feed + 15% fermented rumen content. Samples are observed daily for daily egg production and the last week for egg yolk quality. The results showed that the uses of fermented rumen contents in rations at a rate of up to 15% causeddid not interfere towards daily egg production and could even improve the quality of egg yolk.